2007
DOI: 10.1002/ijc.22406
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for heritable predisposition to epigenetic silencing of MLH1

Abstract: Epigenetic silencing of MLH1 is the most common cause of defective DNA mismatch repair in endometrial and colorectal cancers. We hypothesized that variation in the MLH1 gene might contribute to the risk for MLH1 methylation and epigenetic silencing. We undertook a case-control study to test for the association between MLH1 variants and abnormal MLH1 methylation. Eight MLH1 SNPs were typed in the normal DNA from women with endometrial carcinoma. For these studies, the cases were women whose cancers exhibited ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 25 publications
8
63
1
2
Order By: Relevance
“…14,17,20,21 It is intriguing that the A allele at rs1800734 associates with somatic MLH1 promoter methylation and increased risk of MSI CRC. 23,[31][32][33][34][35] In addition, it has been shown that this polymorphism modifies the efficiency of MLH1/EPM2AIP1 transcription. 36 It is difficult to translate these findings into specific recommendations for these patients and their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,20,21 It is intriguing that the A allele at rs1800734 associates with somatic MLH1 promoter methylation and increased risk of MSI CRC. 23,[31][32][33][34][35] In addition, it has been shown that this polymorphism modifies the efficiency of MLH1/EPM2AIP1 transcription. 36 It is difficult to translate these findings into specific recommendations for these patients and their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in sporadic endometrial and colorectal cancer populations in which an association with this SNP variant has been reported, these have been weak, with modest odds ratios. 7 Thus, a minor elevation in the risk of MLH1 methylation or microsatellite instability observed in some cancer populations may not be replicated in others. This is in contrast to the c.-56C4T SNP (rs16906252) of the DNA repair gene MGMT, which correlates strongly with the presence of MGMT promoter methylation in both colorectal carcinoma and non-neoplastic tissues, illustrating that cis-acting elements can have an instrumental role in gene methylation.…”
Section: Discussionmentioning
confidence: 99%
“…6 The c.-93G4A SNP (rs1800734) within the MLH1 promoter has been associated with an increased risk of microsatellite instability or MLH1 methylation in some colorectal and endometrial cancer populations, but not in others. [7][8][9][10] However, these associations have been disputed on the basis that linkage disequilibrium with pathogenic mutations could not be ruled out in populations with a high incidence of familial cancer. 11 Recently, promoter reporter assays showed that the A allele of this SNP conferred reduced transcriptional activity compared with the G allele, consistent with the notion that this allele might predispose to promoter methylation.…”
mentioning
confidence: 99%
“…Consistent with this model, Chen and colleagues reported an association between the MLH1 293A allele and methylation of the MLH1 promoter in colorectal and endometrial cancer. 22 There is also evidence that promoter methylation and transcriptional silencing of other loci occurs in an allele-specific manner during the pathogenesis of colorectal cancer. 23 However, we cannot exclude the possibility that the MLH1 293G>A polymorphism is in linkage disequilibrium with a highly penetrant germline MLH1 mutation for CRC, although the available evidence would argue against this.…”
Section: Discussionmentioning
confidence: 99%